2015
DOI: 10.1039/c5cp04783h
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical tools to distinguish O-ylides from O-ylidic complexes in carbene–solvent interactions

Abstract: In this paper, we report the geometries and properties of 48 molecular species located on the MP2/6-311++G(d,p) PES of the fluorocarbene-(methanol)3 system. The structures were found by a combination of a stochastic search method, using a modified Metropolis acceptance test, and some hand constructed very symmetrical structures. We use several theoretical descriptors to categorize these species, focusing our attention on the interaction between the carbene carbon and the methanol oxygen, CcO, because this is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…We have found that stochastic‐based search of suitable candidate structures for the mutual AB and Au 4 spatial disposition, and their subsequent gradient‐based optimizations, has proven to be a very successful combination of methodologies. Among stochastic‐based methods, ASCEC has demonstrated to be very effective, both for atomic and molecular clusters of diverse nature . ASCEC is a simulated annealing algorithm in which the Metropolis criterion has been modified in such a way that it is possible to ensure exhaustive scans, moving down from high energy areas to areas of the lowest possible energies for the studied adducts.…”
Section: Methodsmentioning
confidence: 99%
“…We have found that stochastic‐based search of suitable candidate structures for the mutual AB and Au 4 spatial disposition, and their subsequent gradient‐based optimizations, has proven to be a very successful combination of methodologies. Among stochastic‐based methods, ASCEC has demonstrated to be very effective, both for atomic and molecular clusters of diverse nature . ASCEC is a simulated annealing algorithm in which the Metropolis criterion has been modified in such a way that it is possible to ensure exhaustive scans, moving down from high energy areas to areas of the lowest possible energies for the studied adducts.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been pointed out that "water interactions with aliphatic chains are puzzling due to their inability to form hydrogen bonding or favorable electrostatic interaction". 7 This argument ignores the contributions from secondary hydrogen interactions (those where the proton in the HB comes from a C-H bond), [32][33][34][35][36][37][38][39][40][41] and more specically, it overlooks stabilizing orbital interactions. [42][43][44][45] Recognizing present limitations, the same authors stated in a recent work 3 "there have been no signicant efforts in using modern quantum chemical methods to derive plausible forces from a true ab initio procedure".…”
Section: Introductionmentioning
confidence: 99%
“…The shift in the observed wavenumbers of these bands from computational predictions can be explained by solvent-specific interactions at the carbene centre to form an ylidic complex in which there is partial electron donation from the nucleophile to the vacant p-orbital of the carbene centre. 36 Previous reports have identified similar solvent-dependent shifts in the electronic spectra of singlet carbenes. 37 In cyclohexane, decay of singlet carbene bands should be dominated by the stepwise WR because reaction with solvent is not expected.…”
Section: Singlet Carbenementioning
confidence: 67%